Z rodowodu klasycznego prawa naturalnego - Szadok-Bratuń, Aleksandra; Bratuń, Marek (Studia Prawa Publicznego, 2019)
The issue of natural law has been mentioned by almost all philosophers of law, from the classical ones of ancient Greece to contemporary postmodernists, and is presented in various ways. In compliance with Cicero’s observation that “history is the herald of the future” we have attempted to go back to the sources and to start our considerations ab ovo. The historical review does not address systematically the issue discussed here, and only serves to properly explain what natural law in a classical reflection of ius naturale is. Therefore, our approach to the classical natural law has been narrowed down to three selected sophists, Socrates, Plato and Aristotle, and their views of ius naturale in opposition to ius positivum have been briefly outlined. The article consists of two parts: the first one entitled From Heraclitus to Socrates and the second entitled From Plato to Aristotle. The first part presents sophists’ views on the law of nature. It is worth noting that sophists did not analyse the essence of the law of nature; they were primarily interested in the relationship of the law of nature to positive law. Thus Socrates, by deriving the existence of universal and unchanging laws from human nature, gave birth to the doctrine of natural law with unchanging content. The second part contains the views of Plato and Aristotle on the question of the law of nature. Plato is considered to have discovered the ideal trend of natural law, although in his dialogues the term “law of nature” is not found. It was the theory of Plato’s ideas that became the model for the concept of lex aeterna as an arrangement of divine ideas. Whereas, Aristotle distinguished two types of good that law puts before man, and accepts them as the basis for the dichotomous division of laws. He described good that is indifferent to man, which due to specific circumstances becomes the object of his desire, as positive law. Good that is closely related to the nature of man, which is always and everywhere the object of his desire, is good indicating the natural law.